Managers’ perception of organizational culture and organizational communication - (:unkn) unknown (Kamla-Raj Enterprises, 2015)
Examination of communication in organizations in a cultural context can provide a different point of view to managers for purposes of resolution of communication problems. Besides, determination of dominant communication tendency in an organization can be an element which needs to be prioritized for structuring of organizational processes. This study is intended to identify the relation between sports managers’ perception of organizational culture and organization communication. In the research, survey form has been used as data collection tool. These survey forms contain organizational culture and organizational communication scales. Research samples consist of 200 sports managers selected by random sampling method. As the result of the research, a direct relation between organizational culture and organization communication has been found. © Kamla-Raj 2015.
Keywords: Communication; Cultural context; Socialization; Sports manager; Survey